Data from Public Agencies - Språkrådet (Institute for Language and Folklore, 2020)
Language data in the form of translation memory, parallel texts and term resources, from different organisations, most of them public agencies.

Purpose:

Language data in the form of translation memory, parallel texts and term resources, from different organisations, most of them public agencies.

Språkdata i form av översättningsminnen, parallella texter och termresurser från olika organisationer, de flesta myndigheter.

Syfte:

Språkdata i form av översättningsminnen, parallella texter och termresurser från olika organisationer, de flesta myndigheter.
Myndighetsdata
Keywords: public administration; offentlig förvaltning; SOCIETY AND CULTURE; SAMHÄLLE OCH KULTUR; Social Sciences; Samhällsvetenskap; Languages and Literature; Språk och litteratur; Public Administration Studies; Studier av offentlig förvaltning